Actividades extractivas entre la tradición y la legislación. Saberes entre musgos y tierra de capote en el corregimiento de Santa Elena, Medellín (2012)
ABSTRACT: This article aims to show the struggles between settlers, environmental authorities and land owners around the extraction of forest materials in the basin of Piedras Blancas at Santa Elena village in the municipality of Medellín. The research that led to the present work was founded by the Empresas Públicas de Medellín (EPM), Corantioquia and the Universidad de Antioquia in 2006. The main focus of interest of this article is the dialogue between local and institutional knowledges, which makes visible the role of the other (i. e. the peasant) as a constitutive part of the forest. The geographical areas where these research was conducted are the Piedra Gorda vereda, and two sectors within it: El Cerezo and El Hoyito. The results obtained reveal a collector peasant (musguero) whose environmental practices have commonly been invisible. The environmental laws argue that musgueros work illegally; however, their knowledges and initiatives, have not been properly taken in account.